Inside terrorism - Hoffman, Bruce (Columbia studies in terrorism and irregular warfare, 2017)
“Hoffman examines the demographics of contemporary terrorist leaders and recruits; the continued use of suicide bombers; and the likelihood of a chemical, biological, radiological, or nuclear terrorist strike. He also considers the resurgence of violent antigovernment militants, including white supremacists and opponents of abortion. He argues that the war on terrorism did not end with Osama bin Laden's death and that ongoing instability and strife in Syria, Iraq, Afghanistan, Libya, and Yemen, among other places, will both sustain terrorist movements and have broad implications for domestic and international security around the globe.” (Publisher's description)